2020
DOI: 10.1177/0144598720915534
|View full text |Cite
|
Sign up to set email alerts
|

Source rock types, distribution and their hydrocarbon generative potential within the Paleogene Sokor-1 and LV formations in Termit Basin, Niger

Abstract: The Paleogene lacustrine mudstone is one of the most important sets of source rocks in Termit Basin, Niger. However, studies on the Paleogene source kitchen are scarce. In this study, the source rock types, spatial distribution and their hydrocarbon generative potential within the Paleogene Sokor-1 and LV formations are systematically evaluated. A total of two third-order sequences (SSQ1 and SSQ2, from the bottom to top) and six systems tracts were identified in the Sokor-1 Formation, while the LV Formation ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…These results suggest a cleaner and more consolidated reservoir sandstone interval in wells_2 and _3 than in wells_4, _5 and _9. These variations could be attributed to differences in the environment of deposition, burial depths and diagenetic alterations across wells resulting to increased matrix stiffness at reduced porosity and high elastic wave velocities in wells _2 and _3 than the low velocity sands in wells_4, _5 and _9 (Avseth et al 2000(Avseth et al , 2010Chopra and Marfurt 2006;Lai et. al.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest a cleaner and more consolidated reservoir sandstone interval in wells_2 and _3 than in wells_4, _5 and _9. These variations could be attributed to differences in the environment of deposition, burial depths and diagenetic alterations across wells resulting to increased matrix stiffness at reduced porosity and high elastic wave velocities in wells _2 and _3 than the low velocity sands in wells_4, _5 and _9 (Avseth et al 2000(Avseth et al , 2010Chopra and Marfurt 2006;Lai et. al.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…These formations are penetrated and dissected by northwest-southeast (NW-SE) synthetic and north-northwest south-southeast (NNW-SSE) antithetic normal faults, respectively (Fig. 3), and northeast-southwest (NE-SW) transpressional anticlines (Lai et. al.…”
Section: Geology Of the Study Areamentioning
confidence: 99%
“…Source rocks can only be evaluated using regional geological and seismic data (Mi et al, 2007;Liu et al, 2007;Cao et al, 2009;Gu et al, 2011), applied sequence stratigraphy (Liu et al, 2007;Huang et al, 2015;Lai et al, 2020), seismofacies and seismic attributes (Cao et al, 2009) in regions without wells. Previous studies showed that middle-deep lacustrine, high quality source rocks were developed in Wenchang Formation of Kaiping sag (Pang et al, 1995;Li et al, 2013Li et al, , 2014.…”
Section: Geological Understandings Of Middle-deep Lacustrinementioning
confidence: 99%
“…If geochemical data were obtained, the relationships between TOC and logging curves, TOC and seismic response could be used for fitting the relationships of source rocks on well and seismic data. Thus, quantitative evaluation and prediction of source rock could be achieved (Herron et al, 1988;Hou et al, 1998;Peters et al, 2006;Keym et al, 2006;Lai et al, 2020). For regions with no well, sedimentary facies characterization can provide constrains for the source rocks.…”
mentioning
confidence: 99%
“…Several authors [7] [8] [9] [10] [11], have adopted different approaches to estimate petrophysical properties and their distribution from well log data in LCLR reservoirs in Termit sub-basin. Similarly, [12] [13] [14] [15] [16], have proposed different techniques for fluid and lithology discrimination in reservoir characterizations.…”
Section: Introductionmentioning
confidence: 99%